PERAN MEDIA AUDIO VISUAL BERMUATAN MORAL TERHADAP PENGUATAN SIKAP KEJUJURAN SISWA SD - Muniifah; Habiibah; Ulhaq, Shella Dhiya; Afra, Zulfa Afifah; Hayati, Auliya Aenul (Satya Widya, 2025)
This study aims to analyze the effectiveness of morally-themed audio-visual media in strengthening honesty among elementary school students through character-based learning interventions. The research addresses the urgent need to improve the implementation of honest behavior in primary education, considering the ongoing challenges faced by students due to academic and social pressures. Conducted using a descriptive quantitative approach, the study involved 25 fifth-grade students, with data collected through a validated and reliable closed-ended questionnaire. Four types of media interactive presentations, Wordwall, educational songs, and instructional videos were integrated to stimulate students’ cognitive, affective, and psychomotor engagement. The results demonstrate a positive tendency, with the average honesty perception score reaching 97.75, calculated across all questionnaire indicators using percentage analysis on the Likert scale. These findings reinforce the value of audio-visual media as an innovative solution for character development in elementary schools, while highlighting the critical role of teacher competence in media management. The study’s implications provide an empirical basis for advancing character education in Indonesia’s current curriculum and encourage future research on optimizing digital methods to foster honest behavior.